The Role of Learning Motivation in The Relationship Between Maudhu Usbu'i and Multimedia-Based Learning in Majapahit Islamic Technology Boarding School, Mojokerto - Syeh Aindalloh; Yerry Soepriyanto; Otto Fajariyanto (Eduvest - Journal of Universal Studies, 2024)
Education is a series of programmed learning experiences in the form of both formal and non-formal education, taking place within and outside of schools, and lasting a lifetime. Its purpose is to optimize individuals' abilities so that they can play an appropriate role in life later on. Education within the pesantren (Islamic boarding school) environment has unique characteristics that differentiate it from other educational institutions. In this context, multimedia-based learning has become increasingly relevant for enhancing the effectiveness and appeal of the teaching and learning process. A key factor influencing the success of learning is students' learning motivation. Motivation functions as a driving force that can increase engagement and learning outcomes. This study employed a quantitative approach with a quasi-experimental research design, using a simple random sampling method for the sample selection. Data analysis techniques included descriptive tests, normality tests, homogeneity tests, and two-way ANOVA tests. The research findings indicate that motivation plays a significant role, that both maudhu’usbu’i learning and multimedia have a significant impact, and that the interaction between these two factors also has a significant.